Making the best use of all resources: developing a health promotion intervention in rural Nepal - v Teijlingen, E; Simkhada, P; Stephens, J; Simkhada, B; Rogers, SW; Sharma, S (Health Renaissance, 2012)
DOI: http://dx.doi.org/10.3126/hren.v10i3.7141 Health Renaissance; September-December 2012; Vol 10 (No.3);229-235